DİASPORA İÇİNDE DİASPORA: ALMANYA ALEVİLERİ [DIASPORA WITHIN DIASPORA: GERMAN ALEVIS] - Erdal AKSOY; Zeynep Serap TEKTEN AKSÜRMELİ (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2018)
Whether Turkish population can be defined as a “ethnic minority” or “diaspora” on the basis of how to define Turkish existence in Europe has recently been an issue of discussion. The cultural and political position of of the Alevi community, who migrated to Germany as “guest workers” with other Turkish migrants, in Turkish population in Germany further complicates the issue. In this article, Alevi community living in Germany is analyzed on the basis of the diaspora concept. Although the Alevi organizations in Germany are not homogenous, the organizational activities of Alevis strengthen the claim that Alevis form a seperate diaspora in Germany. Furthermore, other factors enabling political mobilization which are necessary for defining Alevis in Germany as a diaspora, are elaborated in the article. This study does not deny the existence of Alevis as a seperate diaspora in Germany, however, it points out that defining Alevi community as a seperate diaspora in Germany has some political and cultural consequences. Moreover, handling the Turkish existence in Germany as a totality rather than as fragmented diasporas is politically and culturally important to Turkish population in Germany. Therefore, instead of dividing The Turkish diasporic community into smaller different diasporas (such as Alevi, Dersim diaspora etc.), defending and demanding the rights unitedly as a “ethnic minority” and more importantly resisting the assimilation of Turkish people who are described as “foreign worker”, “ immigrant worker” in receiving countries, is considered as a better option for Turkish people in diaspora.